Endurance Exercise Training Reduces Cardiac Sodium/Calcium Exchanger Expression in Animals Susceptible to Ventricular Fibrillation - Kukielka, Monica; Holycross, Bethany; Billman, George E. (Frontiers in Physiology, 2011)
Aim: Increased sodium/calcium exchanger activity (NCX1, an important regulator of cardiomyocyte cystolic calcium) may provoke arrhythmias. Exercise training can decrease NCX1 expression in animals with heart failure improving cytosolic calcium regulation, and could thereby reduce the risk for ventricular fibrillation (VF). Methods: To test this hypothesis, a 2-min coronary occlusion was made during the last min. of exercise in dogs with healed myocardial infarctions; 23 had VF (S, susceptible) and 13 did not (R, resistant). The animals were randomly assigned to either 10-wk exercise training (progressively increasing treadmill running) (S n = 9; R n = 8) or 10-wk sedentary (S n = 14; R n = 5) groups. At the end of the 10-wk period, the exercise + ischemia test provoked VF in sedentary but not trained susceptible dogs. On a subsequent day, cardiac tissue was harvested and NCX1 protein expression was determined by Western blot. Results: In the sedentary group, NCX1 expression was significantly (ANOVA, P<0.05) higher in susceptible compared to resistant dogs. In contrast, NCX1 levels were similar in the exercise trained resistant and susceptible animals. Conclusion: These data suggest that exercise training can restore a more normal NCX1 level in dogs susceptible to ventricular fibrillation, improving cystolic calcium regulation and could thereby reduce the risk for sudden death following myocardial infarction.